2013
DOI: 10.1007/s00439-013-1337-9
|View full text |Cite|
|
Sign up to set email alerts
|

A hypofunctional PAX1 mutation causes autosomal recessively inherited otofaciocervical syndrome

Abstract: Otofaciocervical syndrome (OFCS) is an autosomal recessively inherited disorder characterized by facial dysmorphism, external ear anomalies with preauricular pits and hearing impairment, branchial cysts or fistulas, anomalies of the vertebrae and the shoulder girdle, and mild intellectual disability. In a large consanguineous family with OFCS from Turkey, we performed whole-exome sequencing (WES) of a single pooled DNA sample of four affected individuals. Filtering for variants with a percentage of alternate r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
54
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(61 citation statements)
references
References 29 publications
5
54
1
Order By: Relevance
“…8 The authors demonstrated that the missense mutation segregating with the disease was a 11 The mouse model strongly support that PAX1 depletion in our patients caused thymus aplasia responsible of the SCID. However, after exome data filtering in the patient and his parents, 32 possibly deleterious homozygous variants remained, but none of them was a strong candidate gene for a myopathy (Table S1, Supporting information).…”
Section: Introductionsupporting
confidence: 58%
“…8 The authors demonstrated that the missense mutation segregating with the disease was a 11 The mouse model strongly support that PAX1 depletion in our patients caused thymus aplasia responsible of the SCID. However, after exome data filtering in the patient and his parents, 32 possibly deleterious homozygous variants remained, but none of them was a strong candidate gene for a myopathy (Table S1, Supporting information).…”
Section: Introductionsupporting
confidence: 58%
“…For example, an association with nasal width was observed at 20p11.22 near the PAX1 gene. Mutations in PAX1 cause otofaciocervical syndrome [46], characterized by facial dysmorphology, including specific nasal features such as a sunken nasal root and excessive narrowing. PAX1 plays a role in chondrocyte differentiation [47], which may explain its association with nasal width, a measure of the distance between the left and right cartilaginous nasal alae.…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly, lacrimal gland defects have not been reported in human aniridia (OMIM 106210), a congenital disorder caused by heterozygous mutations in PAX6 . Instead, patients with otofaciocervical syndrome-2 carrying homozygous PAX1 mutations (OMIM 615560) display lacrimal duct abnormalities, a phenotype shared with the closely related otofaciocervical syndrome-1 (OMIM 601653) that harbors mutations in the EYA1 gene (Pohl et al, 2013). On the other hand, branchiootorenal syndrome-1 (BOR1, OMIM #113650) caused by heterozygous EYA1 mutations and branchiootic syndrome-3 (OMIM #608389) caused by SIX1 heterodeficiency display many overlapping phenotypic traits including lacrimal gland stenosis, suggesting that these two genes may act in the same genetic cascade.…”
Section: The Molecular Mechanism Of Lacrimal Gland Developmentmentioning
confidence: 99%